The Lesser of Two Evils? Explaining Chinese Rural Migrant Workers’ Preference for On-demand Food Delivery Work With Reference to the Legal Framework - Lin, Ou (Social & legal studies, 2025)
Drawing on a series of interviews with on-demand food delivery riders, who are rural migrant workers, this paper seeks to explain the workers’ decision to give up stable jobs in factories in favour of largely unregulated and precarious on-demand work. Focusing on those aspects of the legal framework which shape workers’ decisions, it presents the explanation under the dual banners of ‘income’ and ‘freedom and flexibility’. In terms of income, Chinese law often enables low factory wages and a reliance on overtime; migrant workers view social insurance contributions as a loss; issues with payroll and wage arrears are significant. In terms of freedom and flexibility, insufficient rest rights lead to inadequate breaks for assembly line workers and, compounded by unspecified ‘special working time’ permit physically unbearable shifts without extra compensation. Age and gender discrimination are prevalent both in factories and various sectors. In contrast, on-demand delivery work has relatively low barriers to entry.